Early childhood studies : enhancing employability and professional practice - Ingleby, Ewan (Bloomsbury Academic, 2014)
Early Childhood Studies: Enhancing Employability and Professional Practice explores essential aspects of best practice within children's services in order to enhance employability skills, identifying how and why key aspects of best practice have emerged within children's services. The key elements of professional practice at the centre of the multidisciplinary work in today's children's services are considered, including: different childhoods; child development; enhanced learning; professional skills; inclusion; holistic practice. Each chapter draws together practical.